Effect of black tea on lipid peroxidation in carbon tetrachloride treated male rats - (:unkn) unknown (Freund Publishing House Ltd, 2000)
This study examined the effects of black tea (Camellia sinensis L.) on lipid peroxidation and glutathione levels in carbon tetrachloride (CCl4)- treated male Wistar rats. Three groups of rats formed two control groups and one treatment group. The control groups were fed with a standard diet, while the black tea group were fed the standard diet plus 6% by weight dried black tea leaves. After two months, the rats in the black tea group and in one control group were administered a single dose of CCl4 (1 ml/kg, i.p.) and sacrificed two hours later. Rats in the other control group were administered olive oil in a similar fashion. Lipid peroxide levels in liver and plasma, glutathione (GSH) levels in liver and alanine transaminase (ALT) and aspartate transaminase (AST) activities in plasma were measured. Rats in the black tea group were found to have significantly decreased liver lipid peroxide levels, and ALT and AST activities compared with the rats in the CCl4-treated control group. In addition, liver glutathione levels were decreased in the black tea group. These data suggest that black tea attenuates CCl4-induced hepatic injury.
Keywords: ALT; AST; Black tea; Glutathione; Lipid peroxidation